2022
DOI: 10.1039/d2qo01069k
|View full text |Cite
|
Sign up to set email alerts
|

Rongalite in PEG-400 as a general and reusable system for the synthesis of 2,5-disubstituted chalcogenophenes

Abstract: In this work, we report the use of rongalite in PEG-400 as a general, reusable, efficient, inexpensive and environmentally benign reductive system for elemental chalcogens and its use for the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 147 publications
1
8
0
Order By: Relevance
“…On the basis of the results of the control experiments and previous reports, we propose a plausible mechanism (Scheme ). First, a direct nucleophilic substitution process between 1 and 2 happens to yield species A , which further undergoes dehydration with the assistance of NaOAc to give intermediate B .…”
supporting
confidence: 57%
“…On the basis of the results of the control experiments and previous reports, we propose a plausible mechanism (Scheme ). First, a direct nucleophilic substitution process between 1 and 2 happens to yield species A , which further undergoes dehydration with the assistance of NaOAc to give intermediate B .…”
supporting
confidence: 57%
“…Remarkably, 2,5-disubstituted chalcogenophenes from 1,3butadiynes and elemental chalcogens (Te, S, Se) using rongalite in PEG-400, have successfully been reported by the research team of Schneider (scheme 3). [14] In this method, chalcogen species -acting as the nucleophiles were added regioselectively to the triple bond, which upon subsequent cyclization in 5endo-dig manner afforded a wide variety of the corresponding chacogenophenes. In this study, the authors have employed diverse symmetrical as well as non-symmetrical 1,3-butadiynes consisting of both electron-donating groups (EDGs) as well as electron-withdrawing groups (EWGs).…”
Section: Organochalcogen (S Se Te) Compoundsmentioning
confidence: 99%
“…In the last decades, chalcogens (O, S, Se, and Te) have received great attention for applications in materials. 16,17 Recently, Silveira and collaborators 18 synthesized a series of organoselenium compounds with photophysical properties UV-Vis and steady-state emission fluorescence. In the UV-Vis study, for example, all derivatives revealed transition bands in the ultraviolet and visible window between 270 and 450 nm.…”
Section: Introductionmentioning
confidence: 99%